2000
DOI: 10.1097/00001721-200006000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Textilinins from Pseudonaja textilis textilis. Characterization of two plasmin inhibitors that reduce bleeding in an animal model

Abstract: The incidence of vein-graft occlusion associated with myocardial infarction and thrombosis following the use of the plasmin inhibitor, aprotinin, to reduce blood loss during vascular surgery has prompted the isolation of an alternative kinetically distinct inhibitor of plasmin from the venom of Pseudonaja textilis. This inhibitor has been called textilinin (Txln) and two distinct forms have been isolated from the Brown-snake venom (molecular weight, 6688 and 6692). A comparison of plasmin inhibitor constants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 32 publications
3
97
0
3
Order By: Relevance
“…There were notable differences in proteins in the molecular mass range of 5-10 kDa. It has been reported that short and long neurotoxins and textilinins are known to occur in this size range (3,4,9). By reference to Fig.…”
Section: Separation and Comparative Analysis Of P Textilis Venommentioning
confidence: 95%
See 2 more Smart Citations
“…There were notable differences in proteins in the molecular mass range of 5-10 kDa. It has been reported that short and long neurotoxins and textilinins are known to occur in this size range (3,4,9). By reference to Fig.…”
Section: Separation and Comparative Analysis Of P Textilis Venommentioning
confidence: 95%
“…These include postsynaptic ␣-neurotoxins (2-4), the presynaptic neurotoxin textilotoxin (5-7), phospholipase A 2 s (PLA 2 s) 1 (6,8); serine protease inhibitors (9,10), and a prothrombin activator (11,12). Fry (13) has written a comprehensive review on the properties of venom components from Australian elapids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cone snails have peptides that act as calcium or sodium channel blockers or bind to the nicotinic acetylcholine receptor (Nielsen et al, 2000). Small proteins or peptides found in snake venoms include the PLA 2 phospholipases (Kwong et al, 1989) and Kunitz-type serine protease inhibitors, such as the venom basic protease inhibitor (Chen et al, 2001) and the textilinins (Masci et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To date, six textilinins from Pseudonaja textilis textilis, the Australian Common Brown snake, have been identified by cloning from venom-gland cDNA (Masci et al, 2000). All consist of $60 amino-acid residues.…”
Section: Introductionmentioning
confidence: 99%